2003
DOI: 10.4049/jimmunol.170.8.3977
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Compartmentalization of Toll-Like Receptor 4 in the Mouse Gut

Abstract: Pattern recognition receptors (PRRs), which include the Toll-like receptors (TLRs), are involved in the innate immune response to infection. TLR4 is a model for the TLR family and is the main LPS receptor. We wanted to determine the expression of TLR4 and compare it with that of TLR2 and CD14 along the gastrointestinal mucosa of normal and colitic BALB/c mice. Colitis was induced with 2.5% dextran sodium sulfate (DSS). Mucosa from seven segments of the digestive tract (stomach, small intestine in three parts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
247
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(264 citation statements)
references
References 49 publications
16
247
0
1
Order By: Relevance
“…Our finding that polarized mIC cl2 cells expressed TLR2, TLR4, and TLR5 transcripts and responded to Pam 3 CSK 4 , LPS, and flagellin indicates that the cells carried functional TLR2, TLR4 and TLR5 complexes. This expression repertoire is in line with the reported in vivo expression of these receptors in mouse cecum (Ortega-Cava et al, 2003Singh et al, 2005) and classify mIC cl2 cells as an excellent tool to study the cross-regulation of the TLR2, TLR4, and TLR5 pathways in intestinal epithelial cells.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our finding that polarized mIC cl2 cells expressed TLR2, TLR4, and TLR5 transcripts and responded to Pam 3 CSK 4 , LPS, and flagellin indicates that the cells carried functional TLR2, TLR4 and TLR5 complexes. This expression repertoire is in line with the reported in vivo expression of these receptors in mouse cecum (Ortega-Cava et al, 2003Singh et al, 2005) and classify mIC cl2 cells as an excellent tool to study the cross-regulation of the TLR2, TLR4, and TLR5 pathways in intestinal epithelial cells.…”
Section: Discussionsupporting
confidence: 83%
“…TLR5 can sense flagellin, the major subunit of bacterial flagella (Andersen-Nissen et al, 2005;Hayashi et al, 2001). Under circumstances such as DSS-induced colitis, bacterial infection, or prolonged exposure to high concentration of ligand, expression of TLR2 and TLR4 is subject to change (Ortega-Cava et al, 2003;Totemeyer et al, 2003). In fact, activation of TLR2 or TLR4 through commensal bacteria turns out to be a prerequisite for the protection against epithelial damage (Rakoff-Nahoum et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The localization of TLRs on epithelial cells is variable and cell specific (Gewirtz et al 2001, Hornef et al 2002, Backhed & Hornef 2003, Ortega-Cava et al 2003. While TLR2 and TLR4 have been shown to reside on the cell surface of macrophages (Ortega-Cava et al 2003), in intestinal epithelial cells TLR4 has been shown to localize to the Golgi apparatus (Hornef et al 2002, Backhed & Hornef 2003, indicating that responsiveness of the epithelium may involve some sort of cellular processing.…”
Section: Epithelial Responses To Microbes As a Key Regulator Of Pmn Tmentioning
confidence: 99%
“…While TLR2 and TLR4 have been shown to reside on the cell surface of macrophages (Ortega-Cava et al 2003), in intestinal epithelial cells TLR4 has been shown to localize to the Golgi apparatus (Hornef et al 2002, Backhed & Hornef 2003, indicating that responsiveness of the epithelium may involve some sort of cellular processing. While some controversy exists, it is generally accepted that TLR5, the receptor for the gram negative bacterial product flagellin, is restricted to the basolateral side of the intestinal epithelium (Gewirtz et al 2001).…”
Section: Epithelial Responses To Microbes As a Key Regulator Of Pmn Tmentioning
confidence: 99%
“…It is therefore not surprising that the TLR molecules and elements of their signaling machinery are expressed not only by resident ileal and colonic macrophages but also by components of the intestinal epithelium. [17][18][19] Furthermore, these expression patterns are altered in the context of CD or UC and in the presence of an inflammatory mediator. [20][21][22][23] This evidence, coupled with the observation that MYD88 and TLR4 alleles affected the severity of experimental colitis in the mouse, led us to initiate an assessment of genetic variation within the TLR pathway for association with human IBD.…”
Section: Introductionmentioning
confidence: 99%